Magnetic resonance imaging of interstitial lung diseases: A state-of-the-art review. (August 2019) - Lonzetti, Lilian; Zanon, Matheus; Pacini, Gabriel Sartori; Altmayer, Stephan; Martins de Oliveira, Diogo; Rubin, Adalberto Sperb; Gazzoni, Fernando Ferreira; Barros, Marcelo Cardoso; Hochhegger, Bruno
Abstract: Magnetic resonance imaging (MRI) has been emerging as an imaging modality to assess interstitial lung diseases (ILD). An optimal chest MRI protocol for ILDs should include non-contrast breath-holding sequences, steady-state free-precession sequences, and contrast-enhanced sequences. One of the main MRI applications in ILDs is the differentiation between areas of active inflammation (i.e. reversible stage) and fibrosis. Alveolitis presents high signal intensity on T2-weighted sequences (WS) and early-enhancement on contrast-enhanced MR sequences, while fibrotic-predominant lesions present low signal and late-enhancement in these sequences, respectively. MRI can be useful in connective tissue diseases, idiopathic pulmonary fibrosis, and sarcoidosis. The aim of this state-of-the-art review was to perform a state-of-the-art review on the use of MRI in ILDs, and propose the optimal MRI protocols for imaging ILDs. Highlights: MRI could differentiate areas of reversible active inflammation from irreversible fibrosis. MRI can be useful in connective tissue diseases, idiopathic pulmonary fibrosis, and sarcoidosis. A chest MRI for ILDs should include non-contrast breath-holding, steady-state free-precession and contrast-enhanced sequences.